SOME SCIENTIFIC REFLECTIONS ON MEDICAL PEDAGOGY AND ITS FORMATION AND DEVELOPMENT TRENDS - Feruza Zakirova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article discusses the significance of the potential of medical pedagogy in enhancing the medical competence of the cadets and listeners of the Ministry of Internal Affairs.